Encara un nou testimoni de l'Explanatio in cantica canticorum de Sant Just d'Urgell: el ms. 1515 de la Biblioteca del Monestir de Montserrat - Alturo i Perucho, Jesús (Miscel·lània litúrgica catalana, 2016)
MS 1515 from Montserrat Abbey is a fragment of a codex which is a part of the Explanatio in Cantica Canticorum by Saint Justus of Urgell, in an Italian copy written during the 11th century in the Carolingian minuscule. This is a membrum disiectum of ms 193/4 from the Biblioteca de Catalunya (Library of Catalonia). The leaf allows an ideal reconstruction of the original manuscript sizes, copied by the same scribe who worked on the transcription of ms 193/1 and ms 193/3 from the same national library, membra disiecta in turn of an office lectionary. This essay also examines the textual variations of the two membra disiecta of this commentary by Saint Justus of Urgell and indicates the different interventions of two correcting hands.